Time‐resolved transcriptomics of mouse gastric pit cells during postnatal development reveals features distinct from whole stomach development. Issue 3 (7th November 2022) - Wei, Ying; Xu, Zeqian; Hu, Miaomiao; Wu, Zhongqin; Liu, Axian; Czajkowsky, Daniel M.; Guo, Yan; Shao, Zhifeng
Abstract : Whole‐organ transcriptomic analyses have emerged as a common method for characterizing developmental transitions in mammalian organs. However, it is unclear if all cell types in an organ follow the whole‐organ defined developmental trajectory. Recently, a postnatal two‐stage developmental process was described for the mouse stomach. Here, using laser capture microdissection to obtain in situ transcriptomic data, we show that mouse gastric pit cells exhibit four postnatal developmental stages. Interestingly, early stages are characterized by the up‐regulation of genes associated with metabolism, a functionality not typically associated with pit cells. Hence, beyond revealing that not all constituent cells develop according to the whole‐organ determined pathway, these results broaden our understanding of the pit cell phenotypic landscape during stomach development. Abstract : Here, using in situ transcriptomic data, we show that mouse gastric pit cells exhibit four postnatal developmental stages, which are distinct from whole stomach development. Interestingly, early stages are characterized by the up‐regulation of genes associated with metabolism, a functionality not typically associated with pit cells. These results broaden our understanding of the pit cell phenotypic landscape during stomach development.